Hidden drivers of organisational transformation in Poland: Survival networks amongst state owned and privatised firms in the early 1990s - Beth Kewell (Journal for East European Management Studies, 2002)
Three historical case studies from Polish manufacturing industry are used to evaluate the rise of survival networks in Poland during the early 1990s. The article poses the question of whether survival networks represented a hidden driver of organisational transformation and change in post-Communist Poland? In transition economies such as Poland, survival networks appeared to be governed by interwoven ex-communist elites' and entrepreneurs, of which nomenklatura managers were the dominant group. The paper argues that survival networks may have provided the organisational architecture needed to reinforce elite governance of industry and commerce. – – Drei historische Fallstudien aus der polnischen Industrie sollen den Anstieg von überlebenden Netzwerken in Polen während der frühen 90er veranschaulichen. Der Artikel hinterfragt, ob die überlebenden Netzwerke einen versteckten Einfluss auf die organisatorische Transformation und die Wende im postkommunistischen Polen darstellten. In Transitionsökonomien wie Polen schien es, dass überlebende Netzwerke von miteinander verflochtenen exkommunistischen Eliten und Unternehmern geleitet würden, von denen wiederum Manager der früheren Nomenklatura den grössten Teil ausmachten. Im vorliegenden Aufsatz wird die These aufgestellt, dass die überlebenden Netzwerke die notwendige Organisationstruktur für die Verstärkung der elitären Steuerung von Industrie und Handel geschaffen haben.
Keywords: 650